Nursing domain of CI governance: recommendations for health IT adoption and optimization. (9th February 2015) - Collins, Sarah A; Alexander, Dana; Moss, Jacqueline
Abstract: Context There is a lack of recommended models for clinical informatics (CI) governance that can facilitate successful health information technology implementation. Objectives To understand existing CI governance structures and provide a model with recommended roles, partnerships, and councils based on perspectives of nursing informatics leaders. Design, Setting, Participants We conducted a cross-sectional study through administering a survey via telephone to facilitate semistructured interviews from June 2012 through November 2012. We interviewed 12 nursing informatics leaders, across the United States, currently serving in executive- or director-level CI roles at integrated health care systems that have pioneered electronic health records implementation projects. Results We found the following 4 themes emerge: (1) Interprofessional partnerships are essential. (2) Critical role-based levels of practice and competencies need to be defined. (3) Integration into existing clinical infrastructure facilitates success. (4) CI governance is an evolving process. We described specific lessons learned and a model of CI governance with recommended roles, partnerships, and councils from the perspective of nursing informatics leaders. Conclusion Applied CI work is highly interprofessional with patient safety implications that heighten the need for best practice models for governance structures, adequate resource allocation, and role-based competencies. Overall, there is a notable lack of a centralized CI group comprised of formally trained informaticians to provide expertise and promote adherence to informatics principles within EHR implementation governance structures. Our model of the nursing domain of CI governance with recommended roles, partnerships, and councils provides a starting point that should be further explored and validated. Not only can the model be used to understand, shape, and standardize roles, competencies, and structures within CI practice for nursing, it can be used within other clinical domains and by other informaticians.